Regional national policies in focus of ethnosociologists - Popkov, Yuri V.; Persidskaia, Olga A. (The New Research of Tuva, 2014)
Article describes the work of ethnosocial expedition of Novosibirsk sociologists to study the aspects of ethnosocial processes and ethnonational policies in Siberian regions: Khanty-Mansiysk Autonomous District, Republic of Altai and Novosibirsk Region.